A visit with Viv: Empathising with a digital human character embodying the lived experiences of dementia. (October 2021) - Papadopoulos, Christopher; Kenning, Gail; Bennett, Jill; Kuchelmeister, Volker; Ginnivan, Natasha; Neidorf, Melissa
The Visit, an immersive participatory artwork (viewed on a screen or virtual reality headset), was produced as part of a research programme investigating the subjective experience of dementia and the relational dynamic between people with dementia and others. It invites viewers to engage with a digital human character, 'Viv', as she shares her experiences of living with dementia. The experiences that Viv recounts are based on verbatim accounts from in-depth interviews with four women living with dementia. The artwork was designed with the combined aim of generating insights into the lived experience of dementia and establishing conditions under which viewers might cultivate empathy for the character portrayed. Viewers engaging with Viv were invited to complete pre- and post-engagement measures of state empathy alongside an assessment of emotional distance . State empathy was significantly greater after engaging with The Visit, and correspondingly, there was a significant decrease in emotional distance (aversion), suggesting that the aims were met.